Torque-compensated bundle of artificial muscle to generate large forces. (17th November 2021) - Kim, Kihyeon; Yang, Sang Yul; Park, Jae Hyeong; Jung, Ho Sang; Ko, Jung U; Hwang, Seong Taek; Koo, Ja Choon; Moon, Hyungpil; Rodrigue, Hugo; Choi, Hyouk Ryeol
Abstract: Recently, owing to the significant advancement in the field of soft robots, various studies have been conducted on soft actuators. Among the several soft actuators, the double helix twisted and coiled actuator (DTCA), which is fabricated by coiling spandex and nylon under twisted conditions, exhibits considerable performance in terms of large contractile force/strain and Joule heating capability. However, the DTCA still cannot produce sufficient force for large-scale applications. Bundling the DTCA in parallel is a well-known solution to improve the force. However, excessive bundling results in unnecessary torque, which causes friction in the entire system. In this paper, we propose a DTCA bundle that can generate a significantly higher force than that previously observed in the field of soft robotics. The proposed bundle compensates for the uncoiling torque by bundling DTCAs fabricated in opposite directions. The fabrication conditions were modified experimentally to satisfy the equivalent performance of each type of DTCA. Consequently, they exhibited as similar performance, including the uncoiling torque with an error of less than 8%.